2010
DOI: 10.3109/09513590.2010.533799
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic findings and reproductive outcome of infertile couples referred to an assisted reproduction program

Abstract: It is still undefined whether all the couples entering an assisted reproduction program should undergo to karyotype analysis. The present study was conducted to determine the prevalence of chromosomal abnormalities in a non-selected sample of 1,146 couples referred to assisted reproduction technologies (ART), and to analyze the outcome of pregnancies from couples in whom cytogenetic anomalies were detected. Irrespective of the infertility factor, fertilization was achieved by intracytoplasmic sperm injection (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
3
2
Order By: Relevance
“…The relative frequency of normal or unbalanced gametes appears to depend largely on the chromosomes involved, the size of the region involved, the presence of heterochromatin, location of the breakpoints, and likelihood of recombination events taking place within the translocated segments (Tempest and Simpson, 2010). In agreement with the findings of a recent study (Antonelli et al, 2011) on infertile men with Y chromosome aberrations (microscopic chromosomal abnormalities with or without AZF deletions), we also emphasize that the translocations observed by us could have led to defects in the pairing and recombination of homologous chromosomes during meiotic prophase I. Tiboni et al (2011) reported that 4.5% of azoospermic and severe oligozoospermic men, 0.53% of mild oligozoospermic men, and 1.21% of normozoopsermic infertile men had chromosomal abnormalities. Consequently, it is important to screen infertile men for chromosomal abnormalities, although they represent a small fraction (∼2%) of infertile cases in our cohort of samples.…”
Section: Discussionsupporting
confidence: 93%
“…The relative frequency of normal or unbalanced gametes appears to depend largely on the chromosomes involved, the size of the region involved, the presence of heterochromatin, location of the breakpoints, and likelihood of recombination events taking place within the translocated segments (Tempest and Simpson, 2010). In agreement with the findings of a recent study (Antonelli et al, 2011) on infertile men with Y chromosome aberrations (microscopic chromosomal abnormalities with or without AZF deletions), we also emphasize that the translocations observed by us could have led to defects in the pairing and recombination of homologous chromosomes during meiotic prophase I. Tiboni et al (2011) reported that 4.5% of azoospermic and severe oligozoospermic men, 0.53% of mild oligozoospermic men, and 1.21% of normozoopsermic infertile men had chromosomal abnormalities. Consequently, it is important to screen infertile men for chromosomal abnormalities, although they represent a small fraction (∼2%) of infertile cases in our cohort of samples.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding karyotype analysis in IVF-ICSI population, we observed a prevalence of chromosomal anomalies of 1.53% and 1.82% in women and men, respectively. The prevalences were higher than those observed in general population but are lower than those reported in the literature [16][17][18][19][20].…”
Section: Discussioncontrasting
confidence: 77%
“…As with any technique in assisted reproduction, the long term consequences of ICSI remain an issue of concern. In particular, an increase in chromosome abnormalities (Tiboni et al, 2011;Woldringh et al, 2010) and an increase in imprinting disorders in ICSI-conceived newborns have been observed (Neelanjana and Sabaratnam, 2008). These findings might be due to the selected population undergoing fertility treatments or to the procedures themselves.…”
Section: Introductionmentioning
confidence: 98%